GGE biplot for stability and adaptability in cashew tree clones - Gilberto Ken Iti Yokomizo; Francisco das Chagas Vidal Neto; Kuang Hongyu; Levi de Moura Barros (Agro@mbiente On-line)
The interaction genotype versus environment makes it difficult the genetic improvement of the species for the selection of more adapted and stable genotypes. Thus, the objective of this work was to evaluate new clones of early dwarf cashews, in terms of stability and adaptability, employing the GGE biplot methodology. The experimental design was based on randomized blocks with four replications and 15 treatments (different clones). The variables evaluated were cashew production per plant (PCP), average mass of chashew (MMC) and early harvest (PRE). The clones G1 and G3 for MMC, G15, G2, G14 and G8 for PRE and G3, G10 and G2 for PCP approached the ideotype; the clones identified as top for each characteristic were not coincident; the majority of the clones were stable for MMC, while for PRE and PCP were not stable; the clone G4 had the best average in PRE, but with low stability; in the GGE biplot the environments A3 for MMC, A4 to PRE and A5 for PCP were the most discriminating; all environments had greater contribution in the differentiation of clones in PRE and MMC, for PCP were the environments A4 and A5; in relation at the average representativeness the environments A1 in MMC and A2 for PRE and PCP stood out.